Upconversion nanoparticle-decorated gold nanoshells for near-infrared induced heating and thermometry. Issue 34 (17th August 2017) - Nigoghossian, K.; Ouellet, S.; Plain, J.; Messaddeq, Y.; Boudreau, D.; Ribeiro, S. J. L.
Abstract : The present work involves the design of a multifunctional system based on gold nanoshells (AuNSs) decorated with lanthanide-based upconversion nanoparticles (UCNPs) intended as an optical heater and temperature probe at the nanoscale. Abstract : The present work involves the design of a multifunctional system based on gold nanoshells (AuNSs) decorated with lanthanide-based upconversion nanoparticles (UCNPs) intended as an optical heater and a temperature probe at the nanoscale. The synthesis of NaGdF4 UCNPs doped with ions Yb 3+ :Er 3+ was performed via thermal decomposition of lanthanide fluoride precursors at high temperatures (>300 °C) in the presence of a coordinating ligand (oleic acid). UCNPs were synthesized at three different temperatures (310, 315 and 320 °C) and characterized in terms of morphological, structural and emission properties. In view of the intended biological applications, the surface of hydrophobic oleate-capped UCNPs was modified using a silica coating to achieve sufficient water dispersibility, through a modified Stöber process using a reverse micro-emulsion method. Monodisperse NaGdF4 :Yb 3+ :Er 3+ upconversion nanocrystals (∼25 nm dia.) were obtained in cubic (at 310, 315 °C) and hexagonal (at 320 °C) phases. The UCNPs in the hexagonal phase were shown to be more suitable as temperature sensors, due to their lower red-to-green emission ratios and higher thermal sensitivities. The emission spectrum of NaGdF4 :Yb 3+ :Er 3+ (oleate- or silica-coated) UCNPs was recorded at different temperatures in the vicinity of the physiological range (20–70 °C) and presented suitable properties for application as temperature sensors, such as excellent linearity ( r 2 > 0.99) and sensitivity (>3 × 10 −3 K −1 ). The heating capacity of AuNSs@UCNPs was verified by monitoring the Er 3+ emission, showing their potential for application as a hyperthermia agent controlled using a nanothermometer function.